Aspidosperma nitidum reduces parasite load and modulates cytokines in BALB/c mice infected with Leishmania (Leishmania) amazonensis - Brígido, Heliton Patrick Cordovil; Varela, Everton Luiz Pompeu; Quadros Gomes, Antônio Rafael; Neves Cruz, Jorddy; Correa-Barbosa, Juliana; Siqueira, José Edson de Sousa; Chagas, Cristian Kallahan Silva; Marinho, Andrey Moacir do Rosário; Almeida Carneiro, Liliane; Coelho-Ferreira, Márlia Regina; Percário, Sandro; Dolabela, Maria Fâni (Frontiers in Chemistry, 2024)
The lack of vaccines shows the need for alternative leishmaniasis treatments. In vitro study previously demonstrated the leishmanicidal activity of Aspidosperma nitidum extracts. This study describes for the first time, the antileishmanial activity of A. nitidum extracts in infected Balb/c mice and its immunomodulatory effect. The extract (EE) was obtained by maceration of the peel powder with ethanol, which was fractionated by acid-base partition, originating the alkaloid (FA) and neutral (FN) fractions. EE and FA were analyzed using mass spectroscopy. Daily intragastric treatment was performed with EE and FA, at doses of 200 mg/kg and 400 mg/kg, in Balb/c mice with 28 days of infection by Leishmania amazonensis. A thickness gauge was used to assess the progression of the lesion and the MTT method to determine the parasite load in the spleen. The quantification of IL-10 and IFN- was performed by ELISA. Analysis of the mass spectrum of EE indicated the presence of the alkaloids corynantheol and yohimbine, while in FA the alkaloid dihydrocorynantheol was identified. To elucidate the mode of interaction of these alkaloids with the TR protein, molecular target of antileishmanial drugs, we used molecular modeling approaches such as docking, molecular dynamics simulations and free energy affinity. Treatment with EE for 28 days at the highest dose tested, significantly reduced the size of the lesion. EE and FA after 28 days of treatment showed dosedependent antileishmanial activity, which reduced the parasite load in the spleen of infected mice by 42.5% and 22.1%, respectively. Both EE and FA presented immunomodulatory effect, as they decreased IL-10 expression and increased IFN-y levels. The effectiveness of A. nitidum in the treatment of cutaneous leishmaniasis was proven in this study. The results obtained in silico demonstrated that the compounds are capable of interacting with the catalytic residues of the TR. The affinity energy results demonstrated that the complexes formed are favorable for enzymatic inhibition. The alkaloids present in the plant have demonstrated not only antileishmanial activity, but also the ability to modulate the host's immune response. These promising results open perspectives for developing more effective and comprehensive treatments against cutaneous leishmaniasis.